2010
DOI: 10.1111/j.1540-6288.2010.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

Investment Irreversibility, Cash Flow Risk, and Value‐Growth Stock Return Effects

Abstract: We simulate results from a simple real options model to provide insight into the value-growth stock return anomaly. In our model, firms possess either single ("value" firm) or multiple ("growth" firm) investment opportunities. Our model predicts that growth firms: (1) invest sooner, (2) exhibit greater continuity in capital expenditure over time, (3) have lower book-to-market ratios, and (4) generate lower rates of return than value firms. Copyright (c) 2010, The Eastern Finance Association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
1
0
5
Order By: Relevance
“…Research on the effect of liquidity on the firm value has been done by several scholars. Chen, et al (2016), Van-Heerden and Van-Rensburg (2016), Azmat (2014) and Prombutr et al (2010) showed a positive effect of liquidity on firm value.…”
Section: Liquidity and Firm Valuementioning
confidence: 94%
“…Research on the effect of liquidity on the firm value has been done by several scholars. Chen, et al (2016), Van-Heerden and Van-Rensburg (2016), Azmat (2014) and Prombutr et al (2010) showed a positive effect of liquidity on firm value.…”
Section: Liquidity and Firm Valuementioning
confidence: 94%
“…Örneğin, yatırım fonu sektörünün büyük firmaların-dan Morningstar ve Lipper Analytical Services şirketleri fonlarını değer ve büyüme kategorilerine ayırırken, F/K ve/veya PD/DD rasyolarının yanı sıra piyasa kapitalizasyonu boyutunu da kullanmaktadırlar (Tengler, 2003: 145 Değer firmalarının düşük F/K rasyolarına sahip olmalarının nedeni, değerlerinin hali hazırdaki aktiflerine bağlı olmasıdır. Yine bu nedenle, söz konusu firmaların PD/DD rasyoları da düşüktür (Prombutr, Lockwood ve Diltz, 2010).…”
Section: Değer Hisse Senetleriunclassified
“…Büyüme hisse senetlerinin yüksek F/K rasyo değerlerinden satılmasının nedeni, yatırımcıların Büyüme firmaları tarafından gelecekte yapılacak yatırımlardan beklediği üstün performans nedeniyle bugünden ödeme yapmaya istekli olmalarıdır. Bunun sonucu olarak, söz konusu firmalar aynı zamanda yüksek PD/DD rasyosuyla karakterize olurlar (Prombutr, Lockwood ve Diltz, 2010).…”
Section: Büyüme Hisse Senetleriunclassified
See 2 more Smart Citations